Soviet Commanders’ Courses on the Ukrainian Territory During the Years of the Civil War 1919–1921: the History of Their Foundation and Work - Tychyna, Iryna (Pedagogical Discourse, 2015)
The article studied the history of foundation of the Soviet military educational institutions on the territory of Ukraine in 1919–1921. The structure and the tasks of the military educational institutions were defined and the number of the institutions and courses which worked on the territory of Ukraine were established. The work of those institutions was reflected and the questions of the short-term courses system reformation into normal military schools were disclosed. The question of the formation of the first national military educational institution on the territory of Soviet Ukraine The Red Sergeant Majors’ School was depicted . The archival documents of the Central state archives of the superior authorities and governance, the Central state archives of social associations of Ukraine, research works, monographs and the articles of the Ukrainian, Russian and Soviet scientists were used for the article. Due to these, there were analyzed the historic experience of the system formation of the military educational institutions on the territory of Ukraine during the continuing war and also achievements and errors of the Soviet military education formation of the studied period.